Excess Gestational Weight Gain in Pregnancy and the Role of Lifestyle Intervention - Goldstein, Rebecca; Teede, Helena; Thangaratinam, Shakila; Boyle, Jacqueline (Seminars in Reproductive Medicine, 2016)
With increasingly adverse lifestyles, young women in many countries have rapid weight gain and rising obesity. In keeping with this, most pregnant women exceed recommended gestational weight gain (GWG) and then retain weight postpartum. The consequences of excess GWG include maternal risks during pregnancy, neonatal risks and maternal obesity and chronic disease longer term, presenting a significant public health and economic burden worldwide. This article discusses the adverse maternal and infant risks with excess GWG apparent from observational studies, summarizes the existing guidelines for optimal GWG and highlights the need for further research to identify optimal GWG recommendations across the different ethnicities and weight ranges.We also review the evidence for lifestyle interventions in pregnancy to prevent excess GWG and highlighting the work underway to integrate large scale meta-analyses of individual patient data from lifestyle intervention studies to inform clinical practice beyond current observational data. Finally, we address the need to implement lifestyle interventions into routine pregnancy care to improve short and long term maternal health outcomes.
Keywords: gestational weight gain (GWG); outcomes; intervention; body mass index (BMI)